RECOGNISI MULTI-STRATEGI DALAM STIMULASI KEMAMPUAN MENYIMAK ANAK USIA DINI PADA PENGAJARAN BAHASA RESEPTIF - Hadi, Saptono (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The research focused on exploring effective strategies for learning receptive language in an effort to foster stimulus-response to improve AUD language acquisition skills. The SLR research method emphasizing library review was used to analyze ten journals highlighting strategy development in improving the quality of education. Using a descriptive qualitative approach, this study identified effective strategies in the stimulation of early childhood listening skills in receptive language teaching. Data were collected through text observation, content analysis, and documentation. It shows that stimulation of AUD language teaching can be achieved through various methods, supporting cognitive, social, and emotional development. This abstract summarizes the main findings from ten research articles that discuss effective strategies in the context of language teaching in AUD.